The simile and metaphor in translation of Yemeni spoken Arabic common names of animals and supernatural creatures into English: A socio-pragmatic approach - Ali Mohammed Saleh Al-Hamzi; Mangatur Nababan; Riyadi Santosa; Muhammed Yunus Anis (Cogent Arts & Humanities, 2023)
This study examines the sociopragmatics of animal and supernatural creatures’ names in Yemeni Arabic (YA) and their translation into English. The study aims to identify the most effective English translations of these metaphors by sending a questionnaire to 43 native English speakers (NESs), focusing on Target Language metaphors and similes (TL) and using Abdul-Raof’s (2006) framework to classify similes. The findings indicate that YA dialects use animal and supernatural creatures’ names to convey meanings, feelings, and intents, while NESs preferred to use detailed similes that incorporate both feature and element. Unlike YA, which accepts all three types of metaphor and simile to address humans using animal and supernatural creatures’ names, most NESs rejected the metaphor, which lacks simile. These findings suggest that animal and supernatural creature names are translated differently in the two languages and cultures, highlighting potential differences in cultural aspects. Generally, this study contributes to our understanding of the sociopragmatics of language use in different cultures and their impact on cross-cultural communication. The findings suggest the need for further research into the translation of animal and supernatural creatures’ names in different languages and cultures.